Perceived desirability and firm’s intention to adopt business to business e-commerce: A test of second-order construct - Alsaad, Abdallah; Mohamad, Rosli; Ismail, Noor Azizi (American Scientific Publishers, 2015)
The adoption of Business to Business E-Commerce (B2B EC) is one of the issues in Information System domain that attract considerable investigations.In view of the complexity of dealing with B2B EC, researchers acknowledge the need to incorporate multiple theoretical causalities to better understand the issue. In line with the advancement of analytical tools nowadays, researchers are now capable to model some theoretical causalities in high level of abstraction which in result reduce the complexity of suggested frameworks. Thus, this study employs Hierarchical Component Model to analyze the Perceived Desirability in the context of B2B EC. The Perceived Desirability is a construct derived from innovation characteristics as proposed by Diffusion of Innovation Theory namely; Perceived Relative Advantage, Perceived Compatibility, and Perceived Complexity.The Perceived Desirability is then proposed to have a direct effect on firms’ intention to adopt B2B EC. Authors tested the proposed model using a data set of 239 marketing managers and purchasing managers in Jordan. The findings confirm conceptual property of Perceived Desirability of B2B EC matches with reflective-formative type of Hierarchical Component Model. Moreover, Perceived Desirability found to be a strong predictor of behavioral intention.